PEMAKNAAN AJARAN TAUHID DAN SHOLAT BAGI MUALAF TIONGHOA DI KOTA PEKANBARU - Mardiyanti, Rina; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Tionghoa etnic as one of minority etnic in Pekanbaru become an interest study. Religious conversion actually is not easy. They will get many conflict come from their family and also the environment. Transcendental experiences can influence their conviction and trust to Allah SWT. Mualaf Tionghoa has different times to adapt for prayer continuously. This study aims to show the motives, the meaning of tauhid learning and prayer. Both of them are distinguishing betweem Islam and other religionThis study uses qualitative research with phenomenological approach. The subject of research is consist of seven mualaf Tionghoa in Pekanbaru who has been chosen using by the snowball technique. The data collection technique is done by depth interview, observation, and documentation. Validity of the data uses trustworthiness including authenticity and triangulations analysis based on method and time.The results showed the motives of mualaf Tionghoa to do religious conversion are transcendental personal motive, rational external motive, pragmatic personal motive, intellectual rational motive, intellectual personal motive, and external judgement motive. The meaning of tauhid learning include (1) tauhidullah of factual, (2) tauhidullah of conceptual, (3) tauhidullah of rational, (4) tauhidullah of complementary. Meanwhile the meaning of praying sholat learning include (1) fundamental meaning, (2) slave meaning, (3) communicative meaning, (4) psychology and medical meaning. This research also showed two type of mualaf Tionghoa as ideal type, semi-ideal type, and labile type.Key Word: phenomenology, mualaf Tionghoa, Tauhid, Praying Sholat